TINJAUAN FENOMENOLOGI ATAS STIGMATISASI SOSIAL PENYANDANG DISABILITAS TUNARUNGU - Karuniasih, Ni Nyoman Mika Putri; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT The discourse on persons with disabilities, especially in hearing impairment social stigmatization could be analyzed through the study of sociology. This study seeks to discuss and explain the experiences of the deafs when they are experiencing, interpreting, even beyond the labeling on their disability. This study used qualitative research methods to the analysis of the theory of phenomenology which focused on three deaf adolescence (middle adolescence), and involve the family, the teacher of SLBB on Sidakarya, and Sanggar Sandi Muni Kumara as one of the deaf dance community in Denpasar City. Based on the results of this study, it is found that social stigmatization could arise from inside and from outside ourselves. Both aspects are mutually influencing and shaping the characteristics of young people with hearing impairment. Characteristics that are formed by the social stigmatization also determine how the deaf adolescence with the limitations of communicating ability to adapt themselves in communities that generally use verbal language. Keywords: Social stigmatization, Disability, Deaf, Phenomenology